2007
DOI: 10.1128/mcb.01369-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuron Survival through an Intersectin-Phosphoinositide 3′-Kinase C2β-AKT Pathway

Abstract: While endocytosis attenuates signals from plasma membrane receptors, recent studies suggest that endocytosis also serves as a platform for the compartmentalized activation of cellular signaling pathways. Intersectin (ITSN) is a multidomain scaffolding protein that regulates endocytosis and has the potential to regulate various biochemical pathways through its multiple, modular domains. To address the biological importance of ITSN in regulating cellular signaling pathways versus in endocytosis, we have stably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 37 publications
(70 reference statements)
11
109
0
1
Order By: Relevance
“…On the following day, cells were transfected with 0.5 g of plasmids encoding proteins fused to pHA-VC155N and pFLAG-VN173N. ITSN1-S, Cbl, and Spry2 BiFC constructs have been previous described (3,25). The VC-Shp2 construct encoding wild-type Shp2 was kindly provided by G. Carnegie (University of Illinois at Chicago) and has been previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…On the following day, cells were transfected with 0.5 g of plasmids encoding proteins fused to pHA-VC155N and pFLAG-VN173N. ITSN1-S, Cbl, and Spry2 BiFC constructs have been previous described (3,25). The VC-Shp2 construct encoding wild-type Shp2 was kindly provided by G. Carnegie (University of Illinois at Chicago) and has been previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…The PI3KC2a Nterminal region appears to inhibit kinase activity, which can be released by clathrin binding (Gaidarov et al, 2001), and PI3KC2a has been implicated in clathrin-mediated endocytosis (Posor et al, 2013). The PI3KC2b N-terminus also binds the scaffold protein intersectin, which promotes increased PtdIns(3)P synthesis (Das et al, 2007). Unlike the PI3KC2a and -b isoforms, PI3KC2c protein interactions have not been tested.…”
Section: Pi3k Protein Domains and Regulatory Subunitsmentioning
confidence: 99%
“…47,48 Recently, we have shown that chronic ITSN deficiency up-regulated extracellular signal regulated kinase (Erk) 1/2 MAPK activity, suppressed the proapoptotic Bad, and altered Smads signaling downstream of the transforming growth factor-b receptor-1, resulting in a proliferative apoptotic-resistant EC phenotype. 12 In a PAH environment, ITSN deficiency and concurrent expression of granzyme B cleavage products of ITSN, able to regulate the p38 to Erk1/2 activity ratio, appear to be critical for initiation of the aberrant EC proliferation.…”
Section: Treatment Of K0mentioning
confidence: 99%